The theoretical description of sucralose cathodic electrochemical determination over a poly(safranin) modified electrode in acidic media - Tkach, Volodymyr; Storoshchuk, Nataliia; Storoshchuk, Bogdan; Oliveira, Sílvio C.; Kryvetskyi, Viktor; Kryvetska, Inna; Kryvetskyi, Igor; Yemelianenko, Nataliia; Narsiia, Valentyn; Yagodynets, Petro; Silva, Adriano; Masna, Zoriana; et al. (My University, 2023)
For the first time, sucralose cathodic electrochemical determination, assisted by the safranin-modified electrode in acidic solutions, has been theoretically described. The correspondent mathematical model analysis has shown that the steady-state stability range is wider than in most systems of electrochemical determination over the pyridinic nitrogen-containing conducting polymer. Moreover, the oscillatory behavior is less probable than in similar systems in acidic media. Nevertheless, it is more probable than in neutral media. Nevertheless, poly(safranin) is an efficient electrode modifier for sucralose electrochemical determination.

Вперше теоретично описано катодне електрохімічне визначення сукралози за допомогою модифікованого сафраніном електрода в кислих розчинах. Аналіз відповідної математичної моделі показав, що стаціонарний діапазон стабільності є ширшим, ніж у більшості систем електрохімічного визначення для піридинового азотовмісного провідного полімеру. Крім того, коливальна поведінка менш імовірна, ніж у аналогічних системах у кислому середовищі. Проте це більш імовірно, ніж у нейтральних ЗМІ. Тим не менш, полі(сафранін) є ефективним модифікатором електродів для електрохімічного визначення сукралози.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; sucralose; conducting polymers; safranin; electrochemical sensors; stable steady-state; сукралоза; провідні полімери; сафранін; електрохімічні датчики; стабільний стаціонарний стан